Insurance-growth nexus in Africa - Balcilar, Mehmet; Gupta, Rangan; Lee, Chien-Chiang; Olasehinde-Williams, Godwin (Palgrave Macmillan Ltd, 2020)
Economic growth may be influenced by insurance market activity through risk pooling, financial intermediations, indemnification against losses, mobilisation of savings and provision of investment opportunities. Over the past few decades there has been increasing interest in the role of the insurance sector in the economic growth of Africa. This study examines whether there is a relationship between the continent's economic growth and insurance market activity (life, non-life, and total). Applying panel estimation techniques that are robust to heterogeneity and cross-sectional dependence to a model of panel data for 11 African countries between 1995 and 2016, we find significant evidence in support of such a relationship. Total insurance penetration has a long-term impact on economic growth, and when disaggregated into its components (life and non-life-insurance penetration), we find evidence in support of short-term and long-term impacts on economic growth in both cases. Our study also confirms the feedback hypothesis, as we find a positive, bidirectional causality between insurance market activity and economic growth. We also find that the contribution from non-life insurance market activity towards economic growth far outweighs that of life insurance market activity.
Keywords: Insurance penetration; Growth; Africa; Panel data; Causality